The Influence of Social Media Marketing, Online Customer Review, Halal Label, and Brand Image on Purchasing Decisions for Somethinc Cosmetic Products (Study on Somethinc Cosmetic Consumers in Purwokerto) - Damayanti, Tri Larisma; Miftahuddin, Muchammad Agung; Astuti, Herni Justiana; Handayani, Erna (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study examines the influence of social media marketing, online customer reviews, halal labeling, as well as brand image on purchasing decisions for Somethinc cosmetic products in Purwokerto. Using a quantitative approach, data from 130 respondents were analyzed with SPSS through multiple linear regression, t-tests, F-tests, and determination coefficients. Findings show that all four variables significantly and positively impact purchasing decisions both individually and simultaneously. Halal labeling exhibits the strongest effect, followed by brand image, online customer reviews, and social media marketing. These findings highlight the importance of integrating digital marketing, leveraging halal certification, and strengthening brand perception to enhance purchasing decisions in the competitive cosmetic industry.